2007
DOI: 10.1177/1352458506070682
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in patients with multiple sclerosis: association with the APOE gene and promoter polymorphisms

Abstract: An association with the epsilon4 allele was evident in this study, but only in cases of severe cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 43 publications
0
15
0
7
Order By: Relevance
“…The isoforms differ by single amino acid substitutions at positions 112 and 158 of the APOE sequence, in which APOE2 has two cysteine residues, APOE3 has a cysteine residue at position 112 and an arginine residue at position 158, and APOE4has two arginine residues at both positions [13,14]. Several reports have shown that the APOE e4 allele is a genetic risk factor for Alzheimer's disease [15] and stroke [16]. Furthermore, APOE polymorphisms may be involved in several neurological diseases, such as multiple sclerosis [17], motor neuron disease [18] and tension-type headache [19].…”
Section: Introductionmentioning
confidence: 99%
“…The isoforms differ by single amino acid substitutions at positions 112 and 158 of the APOE sequence, in which APOE2 has two cysteine residues, APOE3 has a cysteine residue at position 112 and an arginine residue at position 158, and APOE4has two arginine residues at both positions [13,14]. Several reports have shown that the APOE e4 allele is a genetic risk factor for Alzheimer's disease [15] and stroke [16]. Furthermore, APOE polymorphisms may be involved in several neurological diseases, such as multiple sclerosis [17], motor neuron disease [18] and tension-type headache [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has a dose‐dependent effect on age of onset [10] and rate of cognitive decline [11]. Additionally, the ApoE4 genotype may influence the risk, onset, or progression of a number of other neurological conditions, including Wilson’s disease [12], multiple sclerosis [13], Creutzfeldt‐Jakob disease [14], traumatic brain injury [15], anuerysmal subarachnoid hemorrhage [16], cerebral amyloid angiopathy [17], Parkinson’s disease [18], and dementia with Lewy bodies [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the APOE gene, polymorphisms that existed at multiple sites of a promoter region have been discovered at − 491 (A/T transversion), − 427 (T/C transversion), − 219 (G/T transversion), etc., and several studies identified that the difference of DNA sequence in the promoter region influenced the transcription and expression of the APOE gene and the expression level of apoE protein through differential binding of transcription factors Bullido et al, 1998). Accumulated evidence showed that the APOE promoter polymorphism was related to CNS disorder (Lambert et al, 2004;Jiang et al, 2007;Parmenter et al, 2007), but main studies of APOE promoter polymorphism focused on Alzheimer's disease (AD). One meta-analysis which included 40 studies with 9662 cases and 9696 controls confirmed a significant but modest association between APOE promoter −491A/T and −219T/G polymorphisms and AD susceptibility (Xin et al, 2010).…”
Section: Discussionmentioning
confidence: 98%